Peningkatan Pemahaman Keluarga tentang Gizi Anak Sekolah Dasar melalui Edukasi Berbasis Karakteristik Keluarga - Zulfitrawati Zulfitrawati; Ma’rifat Istiqa Mukty; Nurhidayah Tiasya Sanas; Rini Jusriani; Nina Isywara Kusuma; Andi Ade Ulasaswini; Asrar As (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Nutritional problems among elementary school-aged children remain a critical public health issue in Indonesia. A lack of family understanding regarding the importance of balanced nutrition is one of the key contributing factors to the high rates of stunting and malnutrition. This community service activity aims to improve family awareness of children's nutrition through an educational approach tailored to the families’ social, economic, and cultural characteristics. The program was conducted at SD Inpres Laikang, involving 60 families. The methods included identification of family characteristics, focus group discussions (FGDs), interactive lectures, and pre-and post-test evaluations. The results showed an improvement in nutritional understanding among 87% of participants, along with healthier dietary behavior changes at home. This approach adapts the principles of the Harvard Public Health Nutrition Model, which views the family as a systemic unit in shaping children's eating habits. Education based on family characteristics has proven effective and relevant in supporting sustainable nutrition literacy improvement.